PENGARUH AUDIT DELAY, OPINI AUDIT TAHUN SEBELUMNYA, PERTUMBUHAN UKURAN PERUSAHAAN , GCG , KESULITAN KEUANGAN, TERHADAP PERGANTIAN KAP (Studi Kasus pada Perusahaan Consumer Good yang Terdaftar di Bursa Efek Indonesia Tahun 2012-2016) - Widiastoeti, Hendy; Lestari, Wahyu Tri (JEA17: Jurnal Ekonomi Akuntansi, 2020)
ABSTRACTAn auditor has to maintain his independence. To remain this, there are needed to be an auditor shift. Based on PP NO.20 of 2015, the replacement is only applied to auditors, while for KAP there is no more requirement to move to another KAP. White no more restrictions on KAP replacement, it is interseting to examine what factors are considered by the company to keep replacing KAP in the following year?there are at least five factors that are considered by the client to make KAP changes, namely audit delay, audit opinion, GCG (Good Corporate Govenance), company growth, and financial distress. This research is a type of quantitative research using statistical tools to answer the problem formulation. The population in this study were Consumer Goods companieslisted on the Indonesia stock exchange during the periode of 2012 to 2016. The result of this study found that audit delay, company growth , and financial distress had a significant positive effect on KAP turnover, audit opinion negatively affected turnover KAP, while GCG (Good Corporate Govenance) does not have a significant effect on KAP replacement.